The economics of yield‐driven processes - Bohn, Roger E.; Terwiesch, Christian (Journal of Operations Management, 1999)
AbstractThe economic performance of many modern production processes is substantially influenced by process yields. Their first effect is on product cost — in some cases, low‐yields can cause costs to double or worse. Yet measuring only costs can substantially underestimate the importance of yield improvement. We show that yields are especially important in periods of constrained capacity, such as new product ramp‐up. Our analysis is illustrated with numerical examples taken from hard disk drive manufacturing. A three percentage point increase in yields can be worth about 6% of gross revenue and 17% of contribution. In fact, an eight percentage point improvement in process yields can outweigh a US$20/h increase in direct labor wages. Therefore, yields, in addition to or instead of labor costs, should be a focus of attention when making decisions such as new factory siting and type of automation. The paper also provides rules for when to rework, and shows that cost minimization logic can again give wrong answers.